Exploration of Student Experience in Utilizing Sevima Edlink in Hybrid Learning in the Informatics Education Department - Perada Liat, Angelina Heleni; Sogen, Maria Magdalena Beatrice; Malelak, Jedidya; Sinlae, Desri Alfiyunita; Timu, Randi Yotang (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The implementation of hybrid learning in higher education requires effective learning management platforms such as Sevima EdLink. This study aims to explore the experiences of Informatics Education students at Citra Bangsa University in utilizing Sevima EdLink for hybrid learning. A mixed-methods approach was used, combining qualitative interviews and quantitative surveys. The results show that Sevima EdLink facilitates course management, material access, and assignment submission, although initial challenges exist in navigation and feature use. The announcement feature is effective for oneway communication, but chat and real-time collaboration require improvement. Students appreciate centralized academic information access, despite occasional technical issues. Overall, Sevima EdLink is considered effective in supporting hybrid learning, with recommendations for improving the user interface and real-time communication features.Penerapan pembelajaran hybrid di perguruan tinggi menuntut efektivitas platform manajemen pembelajaran seperti Sevima EdLink. Penelitian ini bertujuan mengeksplorasi pengalaman mahasiswa Pendidikan Informatika Universitas Citra Bangsa dalam memanfaatkan Sevima EdLink pada pembelajaran hybrid. Metode yang digunakan adalah mixed methods, dengan wawancara kualitatif dan survei kuantitatif. Hasil penelitian menunjukkan Sevima EdLink memudahkan pengelolaan perkuliahan, akses materi, dan pengumpulan tugas, meski terdapat tantangan awal pada navigasi dan penggunaan fitur. Fitur pengumuman efektif untuk komunikasi satu arah, namun fitur chat dan kolaborasi real-time masih perlu ditingkatkan. Mahasiswa mengapresiasi akses informasi akademik yang terpusat, meski kendala teknis kadang terjadi. Secara keseluruhan, Sevima EdLink dinilai efektif mendukung pembelajaran hybrid, dengan rekomendasi peningkatan antarmuka pengguna dan fitur komunikasi real-time.